Fraud Pentagon dan Kecurangan Laporan Keuangan: Potret pada Perusahaan Sektor Kesehatan di Indonesia - Salsabilla, Aisyah Azzah; Fitri, Alfiana (E-Jurnal Akuntansi; Vol 33 No 8 (2023), 2023)
Financial statement fraud is an intentional misstatement related to the reporting of company conditions to obscure financial statement users in making decisions. This research was conducted to examine the influence of the five pentagon fraud elements namely pressure, opportunity, rationalization, ability, and arrogance on fraudulent financial statements. This research uses the Beneish M-Score Model to detect potential fraud in financial reports. The data used in this study is secondary data derived from the annual financial reports of health sector companies listed on the Indonesia Stock Exchange during the 2016-2020 period. The sampling method used a purposive sampling method and the total research sample was 13 companies. Hypothesis testing was carried out using logistic regression analysis with SPSS 26.0 software statistical tools. The research results show that pressure has an influence on financial report fraud. Meanwhile, opportunity, rationalization, ability and arrogance have no effect on fraudulent financial reporting. Keywords: Fraud Pentagon; fraudulent financial reporting; Logistic Regression